2017
DOI: 10.1111/jocn.13706
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence screening in emergency department: a rapid review of the literature

Abstract: Aim: The aim of the review was to identify intimate partner violence screening interventions used in emergency departments (ED) and to explore factors affecting intimate partner violence screening in EDs.Background: Intimate partner violence against women is now clearly recognised as a global health and societal issue. Nurses working in emergency and urgent care settings can play a crucial role in identification, prevention and management of intimate partner violence Research exploring optimal methods of IPV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 54 publications
0
109
1
8
Order By: Relevance
“…However, in this study as well as in our previous study [52], we found lower reports among Arab women of IPV screening and receiving information through HCS compared to Jewish women. Previous research showed that IPV screening was important for women who visit the ER [70]. While there is a debate about universal screening for IPV and universal screening for safety and providing universal information and education on IPV [71,72], it is agreed conducting any form of screening can help women disclose abuse, and help healthcare providers to properly respond to, and treat not only the physical and/or sexual, but also the psychological aspects of IPV [26,73,74].…”
Section: The Effect Of Ipv Screening and Information Received On Suppmentioning
confidence: 99%
“…However, in this study as well as in our previous study [52], we found lower reports among Arab women of IPV screening and receiving information through HCS compared to Jewish women. Previous research showed that IPV screening was important for women who visit the ER [70]. While there is a debate about universal screening for IPV and universal screening for safety and providing universal information and education on IPV [71,72], it is agreed conducting any form of screening can help women disclose abuse, and help healthcare providers to properly respond to, and treat not only the physical and/or sexual, but also the psychological aspects of IPV [26,73,74].…”
Section: The Effect Of Ipv Screening and Information Received On Suppmentioning
confidence: 99%
“…Previous studies on barriers to intervene and screen with the IPV/ DVA victims are abundant (Ahmad, Ali, Rehman, Talpur, & Dhingrra, 2016;Sprague, Madden and Simunovic, 2012). Educational needs are identified to be the most prominent preceding aspect (Crombie, Hooker, & Reisenhofer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We already know that healthcare professionals can play a very important role in identifying and referring IPV victims to appropriate services,4 though they are not always effectively prepared to do so. IPV against older women is often less talked about and therefore, their needs are often overlooked 2.…”
Section: Commentarymentioning
confidence: 99%